Effect of laser beam and arc power on weld bead geometry in hybrid laser arc welding of structural steel - Petreski, Martin; Runchev, Dobre; Vrtanoski, Gligorche; Zdraveski, Filip; Stankoski, Marko (Centre for Evaluation in Education and Science (CEON/CEES), 2024)
Hybrid Laser Arc Welding - HLAW combines the advantages of Laser Beam Welding - LBW and Gas Metal Arc Welding - GMAW, resulting in a welding process of high welding speed, less heat input, deeper penetration into the welding material, and increased process efficiency compared to conventional welding processes. The merger of the two heat sources, laser beam and arc, in a single welding process leads to a weld joint characterized by two zones, an upper-wide zone or laser-arc zone and a lower narrow zone or laser zone. This study investigates the impact of laser beam and arc currents on the weld bead geometry in the arcleading hybrid laser arc welding process of 12 (mm) structural steel. Through systematic experimentation, single-pass hybrid laser arc welds were performed in a butt joint configuration with zero-gap at various power settings, laser beam power range 10 - 13 (kW), and arc current range 340 - 400 (A) to determine their influence on weld bead width, height, and depth. The quality level of the hybrid laser arc welds was evaluated according to ISO 12932. The results indicate that increasing laser beam power enhances weld bead depth and narrows bead width, while the arc current is directly related to weld bead height and overall smoothness. The findings show that weld bead geometry is a function of laser beam and arc power ratio, an increased ratio leads to a narrow weld bead and vice versa.